The impact of covid-19 on selected turkish financial indicators: Empirical evidence from the toda yamamoto causality test - ARZOVA, SABRİ BURAK (My University, 2022)
This paper examines the impact of COVID-19 cases and deaths on selected financial indicators in Turkey between March 2020 and July 2020. This study analyzes the causal relationship between COVID-19 and liquidity and risk perception in Turkey. To measure the impact of COVID-19 on liquidity and risk perception in Turkey, financial indicators, such as the BIST100, credit default swap, 2-year Turkish bond yields, and 10-year Turkish bond yields were examined. The stationarity of variables was tested usingunit root tests. Since all variables were stationary at the first difference, the Toda Yamamoto causality test was chosen to examine the causality relationship between variables. According to the Johansen co -integration test, there was a co-integration relationship between variables. The empirical results of the Toda Yamamoto causality test show that there was a unidirectional Granger causality from the number of COVID-19 deaths to credit default swap. Moreover, there was a unidirectional Granger causality from the Turkish bond yields (2-10 years) to BIST 100. However, between March 2020 andJuly 2020, there is no Granger relationship between the number of COVID-19 cases and the selected financial variables.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Çalışma Ekonomisi; Social Sciences and Humanities; Labor Economics and Industrial Relations; Labor Economics; İŞ FİNANSI; Ekonomi ve İş; Sosyal Bilimler (SOC); BUSINESS, FINANCE; ECONOMICS & BUSINESS; Social Sciences (SOC); Muhasebe; İşletme, Yönetim ve Muhasebe (çeşitli); Finans; Sosyal Bilimler ve Beşeri Bilimler; Accounting; Business, Management and Accounting (miscellaneous); Finance; Social Sciences & Humanities; COVID-19; Financial Indicators; Turkey; STOCK-MARKET; INFLUENZA; EPIDEMIC; COVID-19; Financial Indicators; Turkey